The Shallow Water Wave Equations on a Vector Processor - Kinnmark, I.P.E.; Gray, W.G. (Developments in Water Science, 1988)
This chapter discusses the shallow water wave equations on a vector processor. The shallow water equations are used to determine circulation patterns, and maximum and minimum tides at the interior of a fluid body subject to a tidal forcing at the open boundaries of the region. These circulation patterns are of primary interest in a model to determine transport of different species for environmental applications. Another important application is tsunamis. These are waves generated from earthquake under the floor of the oceans. When these waves propagate into shallow regions their celerities decrease and amplitudes increase, and can cause severe flooding. An interesting possibility for use of shallow water equation models is evaluation of schemes for conversion of tidal energy into commercially available energy. The advent of computers exhibiting fast scalar execution, as well as vector processing capability provides a powerful tool for application of simulation models to large field data sets, as well as multiple simulations for parameter identification purposes.